2018
DOI: 10.1063/1.5026861
|View full text |Cite
|
Sign up to set email alerts
|

How proteins modify water dynamics

Abstract: Much of biology happens at the protein-water interface, so all dynamical processes in this region are of fundamental importance. Local structural fluctuations in the hydration layer can be probed by O magnetic relaxation dispersion (MRD), which, at high frequencies, measures the integral of a biaxial rotational time correlation function (TCF)-the integral rotational correlation time. NumerousO MRD studies have demonstrated that this correlation time, when averaged over the first hydration shell, is longer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 131 publications
4
51
2
Order By: Relevance
“…The rotational motion of water on biological surface is slowed down compared to that in the bulk. 30,[70][71][72] We find a similar slowing down for the water molecules inside cavity. In addition, we observed that the rotational motion inside protein cavity is highly anisotropic with the rotation of the dipole moment vector being the slowest among all the three orthogonal vectors (Fig.…”
Section: Rotational Anisotropysupporting
confidence: 67%
“…The rotational motion of water on biological surface is slowed down compared to that in the bulk. 30,[70][71][72] We find a similar slowing down for the water molecules inside cavity. In addition, we observed that the rotational motion inside protein cavity is highly anisotropic with the rotation of the dipole moment vector being the slowest among all the three orthogonal vectors (Fig.…”
Section: Rotational Anisotropysupporting
confidence: 67%
“…The computational retardation factors (RF) in this study with respect to the relaxation time of free lysine in water (t bulk = 0.21 ps) are all above 100 (cf. observed via NQR experiments [1][2][3][4][5] and MD simulations [6][7][8][9][10][11][12] as well as the relevant peak in DRS. 18,19 Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these values fit the picture of protein hydration dynamics as reported by a range of experiments and simulations much better than the total TDSS. [1][2][3][4][5][6][7][8][9][10][11][12]18,19 Furthermore, please note that the correlation between t cons and t tot is insignificant (R o 0.25). In other words, the character of local hydration dynamics is obscured by the influence of protein motion and is thus not reflected in the total TDSS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations